Economic effects analysis of environmental regulation policy in the process of industrial structure upgrading: Evidence from Chinese provincial panel data - Yu, Xiao; Wang, Peng (The Science of the total environment, 2021)
As Chinese economy enters the stage of high-quality development from the stage of rapid growth, the economic vitality that relies on the demographic dividend and capital dividend is gradually disappearing. In order to alleviate the downward pressure of the economy and explore a sustainable growth path, Chinese government is seeking to optimize industrial economic structure by strengthening environmental regulations. However, the effect of environmental regulation on the change of industrial structure has not been carefully examined yet. This study constructs a panel model and uses the panel data of 30 provinces in China from 2007 to 2016 to empirically test the economic effectiveness of environmental regulation policies on the upgrading of industrial structure. The results showed that diversified environmental regulation policies can accelerate change in regional industrial structure, and the positive effects of economic incentives and legislative monitoring of environmental regulation policies on the upgrading of industrial structure are significant. However, there are significant differences in the economic performance of environmental regulation policies among regions. The economic effectiveness of environmental regulation policies in the eastern region is better than that in the central and western regions, and the low level of environmental regulation in the central and western regions may trigger the “growth limit” problem. Therefore, in order for environmental regulation policies to better promote the upgrade of industrial structure and promote the high-quality development of the national economy, it is necessary to enrich environmental regulation policy tools, seek precise regulation in the field of the environment, build an environmental information service platform, promote supporting reform in key areas, and support the people's livelihood to alleviate transformation pressure. [Display omitted] •Test the effects of multiple environmental policies on the industrial upgrading.•The level of industrial structure upgrading in China is steadily improving.•Economic incentive policies can accelerate industrial upgrading more effectively.•Economic performance of environmental policies greatly varies among regions.